Differential effect of selected methylxanthine derivatives on radiosensitization of lung carcinoma cells - Malki, A.M.; Gentry, J.; Evans, S.C. (Experimental Oncology, 2006)
Aim: Using caffeine as a reference derivative, this study was performed to investigate how other methylxanthine derivatives, theophylline, 3-isobutyl-methylxanthine and 1,3-dipropyl-7-methylxanthine, sensitize cells to radiation by modifying cell cycle checkpoints and inducing the apoptotic response. The effect of the methylxanthine derivatives was studied in response to gamma and ultraviolet radiation in a human large cell lung carcinoma cell line, null for p53, a normal lung epithelial cell line and the large cell lung carcinoma cell line stably transfected with p53. Methods: Effects of theophylline, 3-isobutyl-methylxanthine and 1,3-dipropyl 7-methylxanthine on cell-radiosensitization in comparison to caffeine tested by clonogenic survival assay, MTT assay, ELISA based apoptotic assay, flow cytometry, caspase-3 activity, TUNEL assay, and western blot analysis. Results: All the derivatives, except 3-isobutyl-methylxanthine, increased tumor cell sensitization to radiation by inducing apoptosis in the p53-null lung cancer cell line. The pattern of cell cycle progression revealed that these derivatives increased the number of cells in G1 phase by abrogating the G2/M checkpoint, directing the cells to apoptose through a p53-independent mechanism. In contrast, 3-isobutyl-methylxanthine was more potent than the other derivatives in radiosensitization of normal lung epithelial cells and the lung carcinoma cells stably transfected with wild-type p53. IBMX increased p53 protein level more than caffeine in lung carcinoma cells stably transfected with wild-type p53. Conclusion: Our results suggest that 3-isobutyl-methylxanthine might function through a p53-dependent mechanism.